I want to elaborate a bit more on how to find this. When working on a problem involving a sequence, a good first step is to look at the numbers and see if anything stands out. For this sequence, we notice that each term is three raised to the *n*th power.

`a_n = 3^n`

This is not a recursive formula, but from this point it is easier to see how to find one. Let's think about what is `a_(n+1)` ? Well, let's plug `n+1` into our formula above:

`a_(n+1) = 3^(n+1) = 3*3^n = 3*a_n`

Therefore we can conclue that

`a_(n+1) = 3*a_n` , or ` a_n = 3*a_(n-1)`

*Write a recursive formula that generates the terms 1,3,9,27,...*

A recursive formula defines a given term of a sequence in terms of previous terms.

For this sequence, let `a_1=1` , and `a_n=a_(n-1)*3` for `n>1` .

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.